COMPARING PATELLAR RESURFACING VERSUS NON-RESURFACING TOTAL KNEE ARTHROPLASTY OUTCOMES: A PROSPECTIVE STUDY. - Gupta, Kanhaiya Lal (Student's Journal of Health Research Africa, 2024)
Background The use of patellar resurfacing in total knee arthroplasty (TKA) is still contentious. The study has sought to elucidate the differences in outcomes between patellar resurfacing and patellar non-resurfacing total knee arthroplasty procedures in individuals undergoing knee replacement surgery. Methods This prospective observational study conducted from July 2021 to July 2023, enrolled 140 patients aged over 50 years undergoing primary TKA for knee osteoarthritis. Based on predetermined criteria, patients were categorized into two groups: those undergoing patellar resurfacing and those not. Validated scoring systems were utilized to assess clinical outcomes, functional gains, and patient satisfaction. The visual analog scale (VAS) was employed to measure pain intensity. Version 21.0 of the SPSS program was used to conduct the statistical analysis. Results Following surgery, both groups (n = 70) showed a considerable increase in functional results, pain relief, and clinical outcomes. Additionally, both groups had high patient satisfaction rates—above 90%. On the other hand, neither the clinical nor functional Knee Society scores (p = 0.185) significantly differed between the two groups. In a similar vein, there was no discernible variation between the two groups' rates of pain relief (p = 0.215) or patient satisfaction (p = 0.467). The frequency of minor problems was similar in each group. Conclusion Both patellar resurfacing and non-resurfacing techniques yielded favorable outcomes in terms of clinical improvement, functionality, patient satisfaction, and pain reduction in individuals undergoing TKA for knee osteoarthritis. Resurfacing the patella should be decided individually, taking the patient's preferences and circumstances into account. Recommendations Further research is warranted to identify specific patient populations that may benefit most from patellar resurfacing or non-resurfacing techniques. Surgeons should weigh the potential benefits and drawbacks of each approach and tailor the treatment strategy accordingly.